The spectral dimension of the branched polymers phase of two-dimensional quantum gravity - Jonsson, T; Wheater, J (1997)
The metric of two-dimensional quantum gravity interacting with conformal matter is believed to collapse to a branched polymer metric when the central charge c>1. We show analytically that the spectral dimension of such a branched polymer phase is four thirds. This is in good agreement with numerical simulations for large c.